Spatial Distribution Characteristics and Relationships of Salt-Based Ions and Nutrients in Old Protected Vegetable Fields - Nanbiao Zhan; Haotian Yang; Jiayang Li; Xiaodi Shi; Binhao Yang; Yuhang Sun; Gengzi Guo; Xiumin Cui (Horticulturae)
To achieve a scientific and objective evaluation of soil acidification, secondary salinization, and nutrient imbalance in old protected vegetable fields (OPVs) with over 30 years of cultivation history, a soil surface breeding vigorous moss was investigated. Here, quantitative laboratory analysis and mathematical statistics were employed to explore the spatial distribution of soil salinity and nutrients, as well as their relationships. The results revealed that OPVs exhibited slightly acidified values. The measured anions and cations in the soil salt composition constituted approximately 77% of the total ions. Among which, Ca2+ was the dominant cation, while SO42− and NO3− were predominant anions. The total water-soluble salt (TDS) content of the surface soil reached 4.52 g kg−1, exceeding the Chinese Saline Soils standard (1.0 g kg−1) by 350%. In the OPVs, nitrate nitrogen was significantly higher than ammonium nitrogen, and available phosphorus and available potassium were generally abundant. Despite exhibited various soil health concerns, a field visit survey presented consistently high and stable yields in OPVs. We hypothesize that this seemingly contradictory finding may be attributable to several factors, including the abundance of divalent cations (Ca2+ and Mg2+), the soil fertility and water retention capacity of unsaturated salt-based suitable soil, as well as good soil aggregate structure. These factors had the potential to reduce the stresses on the soil. This study provided a foundational understanding of the nutrient and salinity status of soils in OPVs, offering valuable data and theoretical groundwork for future research endeavors.